2023
DOI: 10.3390/antiox12081524
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Ameliorates Impaired Ovarian Development, Oxidative Stress, and Disrupted Lipid Metabolism in Oreochromis niloticus Fed with a Diet Containing Olive Oil Instead of Fish Oil

Yifan Tao,
Yifan Pan,
Qingchun Wang
et al.

Abstract: Aquaculture feed containing olive oil (OO) instead of fish oil (FO) can cause oxidative stress and impair gonad development in fish. We determined the effect of dietary OO-induced oxidative stress on ovarian development, and explored whether vitamin E (VE) could mitigate negative effects. Female Nile tilapia (Oreochromis niloticus) were fed for 10 weeks with four diets: 5% OO + 70 mg/kg VE, 5% OO + 200 mg/kg VE, 5% FO + 70 mg/kg VE, or 5% FO + 200 mg/kg VE. Dietary OO reduced the specific growth rate and gonad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…A relatively higher lipid level (180 g/kg) in the diets significantly promoted gonad development of female Chinese sturgeon (Acipenser sinensis) [58]). There have been many studies that have reported the beneficial effects of VE on the growth and development of red crayfish (Cherax quadricarinatus) [59], Nile tilapia (Oreochromis niloticus) [60], and pandani (Pseudotropheus socolofi) [40].…”
Section: Discussionmentioning
confidence: 99%
“…A relatively higher lipid level (180 g/kg) in the diets significantly promoted gonad development of female Chinese sturgeon (Acipenser sinensis) [58]). There have been many studies that have reported the beneficial effects of VE on the growth and development of red crayfish (Cherax quadricarinatus) [59], Nile tilapia (Oreochromis niloticus) [60], and pandani (Pseudotropheus socolofi) [40].…”
Section: Discussionmentioning
confidence: 99%